Feasibility and reproducibility of neurochemical profile quantification in the human hippocampus at 3 T - Bednařík, Petr; Moheet, Amir; Deelchand, Dinesh K; Emir, Uzay E; Eberly, Lynn E; Bareš, Martin; Seaquist, Elizabeth R; Öz, Gülin (NMR in biomedicine, 2015)
Hippocampal dysfunction is known to be associated with several neurological and neuropsychiatric disorders such as Alzheimer's disease, epilepsy, schizophrenia and depression; therefore, there has been significant clinical interest in studying hippocampal neurochemistry. However, the hippocampus is a challenging region to study using (1) H MRS, hence the use of MRS for clinical research in this region has been limited. Our goal was therefore to investigate the feasibility of obtaining high-quality hippocampal spectra that allow reliable quantification of a neurochemical profile and to establish inter-session reproducibility of hippocampal MRS, including reproducibility of voxel placement, spectral quality and neurochemical concentrations. Ten healthy volunteers were scanned in two consecutive sessions using a standard clinical 3 T MR scanner. Neurochemical profiles were obtained with a short-echo (T(E) = 28 ms) semi-LASER localization sequence from a relatively small (~4 mL) voxel that covered about 62% of the hippocampal volume as calculated from segmentation of T1 -weighted images. Voxel composition was highly reproducible between sessions, with test-retest coefficients of variation (CVs) of 3.5% and 7.5% for gray and white matter volume fraction, respectively. Excellent signal-to-noise ratio (~54 based on the N-acetylaspartate (NAA) methyl peak in non-apodized spectra) and linewidths (~9 Hz for water) were achieved reproducibly in all subjects. The spectral quality allowed quantification of NAA, total choline, total creatine, myo-inositol and glutamate with high scan-rescan reproducibility (CV ≤ 6%) and quantification precision (Cramér-Rao lower bound, CRLB < 9%). Four other metabolites, including glutathione and glucose, were quantified with scan-rescan CV below 20%. Therefore, the highly optimized, short-echo semi-LASER sequence together with FASTMAP shimming substantially improved the reproducibility and number of quantifiable metabolites relative to prior reports. In addition, the between-session variation in metabolite concentrations, as well as CRLB, was lower than the between-subject variation of the concentrations for most metabolites, indicating that the method has the sensitivity to detect inter-individual differences in the healthy brain.
Keywords: Molecular Imaging; dospělí; Female; hipokampus; Feasibility Studies; Tissue Distribution; Adult; ženské pohlaví; Proton Magnetic Resonance Spectroscopy; Reproducibility of Results; lidé; biopolymery; Sensitivity and Specificity; molekulární zobrazování; senzitivita a specificita; Algorithms; reprodukovatelnost výsledků; studie proveditelnosti; Male; tkáňová distribuce; Biopolymers; algoritmy; Hippocampus; mužské pohlaví; protonová magnetická rezonanční spektroskopie; Humans